Adipose tissue macrophages and atherogenesis - a synergy with cholesterolaemia - Poledne, R; Králová Lesná, I (Physiological research, 2021)
Excessive LDL cholesterol concentration together with subclinical inflammation, in which macrophages play a central role, are linked pathologies. The process starts with the accumulation of macrophages in white adipose tissue and the switch of their polarization toward a pro-inflammatory phenotype. The proportion of pro-inflammatory macrophages in adipose tissue is related to the main risk predictors of cardiovascular disease. The cholesterol content of phospholipids of cell membranes seems to possess a crucial role in the regulation of membrane signal transduction and macrophage polarization. Also, different fatty acids of membrane phospholipids influence phenotypes of adipose tissue macrophages with saturated fatty acids stimulating pro-inflammatory whereas omega3 fatty acids anti-inflammatory changes. The inflammatory status of white adipose tissue, therefore, reflects not only adipose tissue volume but also adipose tissue macrophages feature. The beneficial dietary change leading to an atherogenic lipoprotein decrease may therefore synergically reduce adipose tissue driven inflammation.
Keywords: ateroskleróza; mastné kyseliny; tuková tkáň; zánět; lidé; Inflammation; Adipose Tissue; Macrophages; Atherosclerosis; Fatty Acids; Humans; makrofágy